(untitled) (Research, Society and Development, 2020)
Objective: to gather and analyze the main findings of the literature related to ADHD and to identify the clinical management adopted by the team responsible for the care of the individual with ADHD. Methodology: The present study is an integrative literature review that brings together studies published in the Virtual Health Library and in the PubMed/MEDLINE and LILACS databases. Results: Among the 196 articles found, after the inclusion and exclusion criteria, 8 were selected for analysis and discussion. Two nuclei of meaning were identified: the relevance of previous diagnosis and psychotherapy and the difficulties in the clinical management of ADHD. Conclusion: The analysis of the studies allowed us to understand the importance of complementary training of primary health professionals in the field of psychiatry, with an emphasis on providing care to people with mental disorders and their different degrees of complexity, and from a wide variety of research on the subject. ADHD and nursing, aiming to contribute to the education and training of this class.